2016
DOI: 10.1371/journal.pone.0166484
|View full text |Cite
|
Sign up to set email alerts
|

Skin Globotriaosylceramide 3 Load Is Increased in Men with Advanced Fabry Disease

Abstract: BackgroundThe X-chromosomally linked life-limiting Fabry disease (FD) is associated with deposits of the sphingolipid globotriaosylceramide 3 (Gb3) in various tissues. Skin is easily accessible and may be used as an additional diagnostic and follow-up medium. Our aims were to visualize skin Gb3 deposits in FD patients applying immunofluorescence and to determine if cutaneous Gb3 load correlates with disease severity.MethodsAt our Fabry Center for Interdisciplinary Therapy we enrolled 84 patients with FD and 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…As such Gb3—the end product which accumulates in lysosomes and is routinely used to diagnose the disease on tissue biopsy—heart, kidney15 and most recently skin16—has so far failed to convince as a suitable plasma or urine marker. A study by Young17 performed on hemizygotes, heterozygotes and healthy controls failed to reliably detect increased Gb3 levels in plasma and urine in heterozygotes and hemizygotes with non-classical mutation.…”
Section: Introductionmentioning
confidence: 99%
“…As such Gb3—the end product which accumulates in lysosomes and is routinely used to diagnose the disease on tissue biopsy—heart, kidney15 and most recently skin16—has so far failed to convince as a suitable plasma or urine marker. A study by Young17 performed on hemizygotes, heterozygotes and healthy controls failed to reliably detect increased Gb3 levels in plasma and urine in heterozygotes and hemizygotes with non-classical mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Skin Gb3 deposits have been demonstrated by using complex techniques such as electron microscopy[ 13 ] but they can also be detected by more simple and rapid techniques such as light microscopy[ 14 , 15 ]. However, by using this latter technique skin Gb3 deposits were not found in all analysed patients[ 15 , 16 ], preventing the use of this approach for diagnostic purposes. The reason of the absence of Gb3 deposits in the skin samples of few FD patients is unknown, although a possible correlation with plasma lyso-GL-3 levels was suggested[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heart and kidneys are the organs of choice as these are most frequently involved. We recently described Gb3 deposits in skin punch biopsies of FD patients as a potential additional diagnostic tool . However, even if the risk for adverse events is estimated low during such an organ biopsy, it is still an invasive method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, myocardial or renal biopsy is recommended in cases where test results are equivocal, to search for the presence and extent of cellular Gb3 deposits . We recently showed that using easily applicable microscopy techniques, Gb3 deposits can be visualized in skin samples . However, although considered to be of low risk , biopsies are invasive.…”
Section: Introductionmentioning
confidence: 99%